Interactive Simulation of Realistic Fluid Movement Based on SPH Method - J L Miao; L J Long; Y H Miao; Y Qin (The international journal of multiphysics, 2023)
With the continuous progress of computer simulation technology, fluid simulation has been developed rapidly, and it has beeen widely used in many fields, especially in engineering compution, game and special effects in movie. Nevertheless, with the increasing requirements of fidelity of the motion and interaction of subjects, fluid simulation requires more realistic simulation results. However, the motion of real fluid and objects is often difficult to be expressed by simple process, which can only be realized by the physical laws in the real world. Physical-based fluid simulation is one of the most challenging research issues due to its complexity in theory and computations. Among numerous fluid simulation models, Smoothed Particle Hydrodynamics (SPH) based fluid simution is the most widely used meshless method to simulate the realistic fluid motion. As a simple and flexible method, SPH partical characteristics make it naturally suitable for fluid simulation modeling and feasible to deal with many fluid simulation computation problems in a robust and stable way. The SPH basic principle, kernel function, discretization scheme and boundary treatments are introduced. The fluid movement is solved by SPH method in accordance with Navier-Stokes equations. The accuracy and stability of the fluid solution equation was improved by correcting the pressure and velocity fields. Secondly, the water surface was modeled and the rendering speed of the fluid surface was optimized by simplifying the fluid particles calculation. The SPH model is developed to simulate impulsive wave generated by dam-break and high speed landslide. It shows the model can simulate the movement process of the fluid fragment and coalescence, and available to simulate the blood, volcanic explosion and tsunami propagation.